Vitamin D receptor and estrogen receptor gene polymorphisms in men with type 2 diabetes: Effects on Bone Metabolism - ÜSTAY, ÖZLEM; YAVUZ, DİLEK; YÜKSEL, MERAL (My University, 2022)
Purpose There is an increased fracture risk in type 2 diabetes mellitus [DM] patients independent of bone mineral density [BMD], both in men and women. Estrogen receptor [ER]-alpha and vitamin D receptor [VDR] gene polymorphisms may predispose patients to increased osteoporosis and fracture risk. This study aims to analyze the relationship of the ER-alpha gene and VDR gene polymorphisms with indicators of bone turnover and BMD in male type 2 diabetic patients. Methods Type 2 diabetic men diagnosed with diabetes for at least one year and healthy controls were included in this cross-sectional study. BMD was measured by dual X ray absorptiometry. Gene polymorphisms were evaluated with polymerase chain reaction-restriction length polymorphism. Serum iPTH, calcium, beta-CrossLaps (cTx), osteocalcin, and free testosterone levels were also evaluated. Results Participants were 141 type 2 diabetic men [55 +/- 8 years] and 100 healthy controls [53 +/- 7 years]. BMD measurements were not statistically different between the groups. While iPTH [p < 0.05] and serum calcium levels [p = 0.03] were higher in men with type 2 DM; beta-CrossLaps [p = 0.0001], osteocalcin [p = 0.005], and free testosterone [p = 0.04] were lower than controls. The differences in terms of the frequencies of VDR Apa, Taq, Bsm, Fok and ER-alpha polymorphisms were not statistically significant between the groups. No relationship was observed between polymorphisms and BMD in both groups. Conclusions VDR and ER-alpha gene polymorphisms seem to have no effect on BMD and bone turnover in men with DM.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; ENDOKRİNOLOJİ VE METABOLİZMA; Klinik Tıp; Klinik Tıp (MED); ENDOCRINOLOGY & METABOLISM; CLINICAL MEDICINE; Clinical Medicine (MED); Endokrin ve Otonom Sistemler; Endokrinoloji, Diyabet ve Metabolizma; Endokrinoloji; Yaşam Bilimleri; Endocrine and Autonomic Systems; Endocrinology, Diabetes and Metabolism; Endocrinology; Life Sciences; Bone density; Diabetes Mellitus; type 2; Male; Polymorphism; genetic; Receptors; calcitriol; Estrogen; MINERAL DENSITY; OSTEOPOROTIC FRACTURES; VERTEBRAL FRACTURES; RISK; TURNOVER; WOMEN; ASSOCIATION; GENOTYPES; MELLITUS; MARKERS; Diabetes Mellitus, type 2; Polymorphism, genetic; Receptors, calcitriol; Receptors, Estrogen